Cassia Gum an Environment-friendly Alternative Thickener in Printing with Natural Dyes - Bains, Sandeep; Sethi, Manisha (International Journal of Bio-resource and Stress Management, 2023)
Natural dyes and natural thickening agents appear to be ideal choice for printing the fabric. This is because natural dyes and thickening agents have better biodegradability and higher compatibility with environment. In addition to this, interest in the use of natural dyes and thickening agents has been growing rapidly due to the result of stringent environmental standards imposed by many countries in response to toxic and allergic reactions associated with synthetic dyes. The aim of present work has been carried out to prepare eco-friendly natural dye printing paste from the Arjun dye Bark extract using natural thickening agent i.e. Cassia tora seed gum. The trials were under taken to block print desized cotton fabric with the prepared printing paste. The recipe was optimized using 2.5% and 5% of concentration of the gum and the best concentration was determined. Two mordants, 5% Alum and 2% Ferrous Sulphate were selected for obtaining change in shade and improvement of colour fastness properties. The block printed samples were evaluated for visual evaluation, colour fastness properties and CIE Lab values. Results of cotton block printed samples with both the mordants exhibited excellent to very good fastness rating for light, washing, rubbing and perspirations. Thus, it was concluded that cotton fabric can be successfully block printed using 5% of natural thickening agent.